Strategies and Recommendations to Enhance Online English Teaching Quality in Higher Vocational Colleges - Wu, Yuguang (Pacific International Journal, 2024)
The rapid growth of the Internet has propelled online teaching into a prominent position in higher education, including vocational English courses. Despite its widespread adoption, online teaching faces significant challenges compared to traditional classroom methods. This study delves into the current landscape of online teaching in vocational English courses, identifying key issues such as the lack of targeted course content, insufficient teaching resources, and low student participation. Drawing on a literature review and utilizing both quantitative and qualitative research methods, including questionnaire surveys and field observations, this study offers insights into the complexities of online teaching. Findings highlight the importance of improving teacher’s technical abilities, fostering active student engagement, optimizing teaching resources and modes, and strengthening online teaching supervision. These strategies are pivotal in enhancing the quality of online teaching and paving the way for further advancements in vocational English education. Future research avenues include exploring innovative teaching models and leveraging emerging technologies like artificial intelligence and virtual reality to enrich the online teaching experience.